Analysis of Tannin and Flavonoid Contents of Green Sirih Leaves (Piper betel linn) of Green Different in Physical Conditions - Sigit Setyabudi; Engkus Ainul Yakin; Sri Sukaryani (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
The purpose of this study was to determine the levels of tannins and flavonoids from green sirih leaves which have different physical conditions. Sirih leaf is used as the object of treatment prior to use beam sun dried for 2 days until the color changes, the weight of time, as well as the start crumbly texture, then followed by a drying method using an oven with a temperature of 40oC. The experimental design research in the form of RAL with using observation samples in the form of sirih leaf flour which was dried using sunlight without oven (P0), sirih leaf flour dried in the sun for 6 hours (P1), 7 hours (P2), 8 hours (P3). Sirih leaves that have been made into flour according to the experimental design are then analyzed for the content of tannins and flavonoids. The results of laboratory analysis are then processed using the SPSS application with ANOVA and Duncan analysis. Results of the analysis indicated that there was a very real effect on the old oven for 40OC to contain tannins and flavonoids (P <0.01), followed different test that produces very real differences occurred between treatments. The results of the use of methods oven for 8 hours at a temperature of 40oC after drying sunlight can increase the tannin content of 0,6% and 0,09% flavonoids from sun drying method without oven. Keywords : Green sirih leaf, Flavonoids, Tannins.